Exercise modulates microRNAs that affect the PTEN/mTOR pathway in rats after spinal cord injury - Liu, Gang (2011)
We investigated microRNAs (miRs) associated with PTEN/mTOR signaling after spinal cord injury (SCI) and after hind limb exercise (Ex), a therapy implicated in promoting spinal cord plasticity. After spinalization, rats received cycling Ex 5 days/week. The expression of miRs, their target genes and downstream effectors were probed in spinal cord tissue at 10 and 31 days post injury. Ex elevated expression of miR21 and decreased expression of miR 199a-3p correlating with significant change in the expression of their respective target genes: PTEN mRNA decreased and mTOR mRNA increased. Western blotting confirmed comparable changes in protein levels. An increase in phosphorylated-S6 (a downstream effector of mTOR) within intermediate grey neurons in Ex rats was blocked by Rapamycin treatment. It thus appears possible that activity-dependent plasticity in the injured spinal cord is modulated in part through miRs that regulate PTEN and mTOR signaling and may indicate an increase in the regenerative potential of neurons affected by a SCI.